Bullying Dalam Pendidikan - Asmuni, Hadiqoh (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
Bullying is an action carried out by a person or group by using powers. That aims to hurt others to get satisfaction both verbally, physically and psychologically which causes the victim to feel depressed, afraid, traumatized and helpless. Bullies are at risk of experiencing a variety of problems both physically and psychologically. Problems that arise include difficulty sleeping, difficulty concentrating, anxiety, depression, dizziness, abdominal pain and even a decrease in learning spirit which has an impact on academic achievement. The perpetrators of bullying are not only seniors or peers in school, many of the teachers do bullying practices without them being aware of which ultimately has an impact on students. To overcome this problem the school together with family and community must work together to always provide positive examples and provide knowledge about the dangers and effects of bullying. Provide information both students and students that bullying is very detrimental.